THE MISSING AGES IN “KUNG FU PANDA 3” MOVIE: A PSYCHOANALYTIC LITERARY CRITICISM - Kusen, Felicia Jessica; Silaen, Gwyneth Lillian; Aripin, Aileen Regina (Yayasan Pendidikan Gereja Masehi Advent Hari Ketujuh Makarios, 2023)
This study aims at showing the connection between Po’s past experiences and his present manifestations. This analysis intends to show the significance of the affection and primal parenting of both parents. A qualitative approach was employed to elucidate and evaluate the psychological concern depicted in this film. Given the narrative's visual medium, the utilization of cinematography in terms of camerawork served to articulate the storyline, environments, and characters. Additionally, the analytical framework of Sigmund Freud's